Mister meddles muddles happy days - Blyton, Enid; Catchpole, Diana Downer, Maggie (Bounty Books London, 2013)
Mister Meddle is a pixie who always tries to carry out good deeds. His actions, however, never turn out as planned: he takes all his neighbour's furniture, believing it to be Aunt Jemima's shopping; he is chased by a bull as he misunderstands Farmer Barley's words to 'mind' it; he accidentally does everyone a favour as he sends Sneaky the magician flying away. Repeatedly resolving not to meddle in everyone's affairs, Mister Meddle is unable to mind his own business